Implementation Of Religious Moderation Values In Students' Certainity And Achievement Learning At The Integrated Mts Nurul Qodiri - Junaidi Haripin; Irhamudin Irhamudin; M. Sayyidul Abrori (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2026)
This study aims to analyze the implementation of religious moderation values in Aqidah Akhlak learning at MTs Terpadu Nurul Qodiri, focusing on the aspects of planning, implementation, and evaluation. This research employed a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The research subjects consisted of Aqidah Akhlak teachers, students, and school stakeholders as supporting informants. The findings reveal that in the planning stage, religious moderation values such as tolerance, justice, and balance have been included in learning instruments such as lesson plans and syllabi; however, they remain general and have not been operationally defined in detailed learning activities. In the implementation stage, various teaching methods such as lectures, discussions, question and answer, role modeling, and habituation have been applied. Nevertheless, lectures still dominate, resulting in limited student participation, while discussion and role-modeling methods are proven to be more effective in internalizing moderation values. In the evaluation stage, assessment is still focused on cognitive aspects and lacks specific instruments to measure students’ attitudes toward religious moderation systematically. Overall, the implementation has been carried out but is not yet optimal. Therefore, improvements are needed in systematic planning, participatory implementation, and comprehensive evaluation to ensure that religious moderation values are effectively internalized in students’ character